COMMUNITY SERVICE EDUCATION HUSBAND'S ASSISTANCE IN RECOGNIZING THE DANGER SIGNS OF PREGNANCY AND CHILDBIRTH AT MAHDALENA CLINIC - Noer Desmie; Deni Irawati; Yuliarni Telaumbanua (Jurnal Masyarakat Indonesia (Jumas), 2025)
The involvement of the husband as the main companion is crucial in supporting the health of pregnant women and accelerating decision-making when emergency conditions occur during pregnancy and childbirth. However, the husband's lack of understanding of the danger signs is often an obstacle in early detection efforts. This community service activity aims to improve the knowledge and skills of husbands in accompanying their wives and recognizing the danger signs of pregnancy and childbirth. The program will be held on July 17, 2025 at the Mahdalena Clinic through interactive counseling methods, early detection simulations, and group discussions. The results of the evaluation showed a significant increase in understanding in participants regarding the active role of husbands in monitoring their wife's health and alertness in dealing with pregnancy danger signs. This education is expected to increase family preparedness in facing medical complications to support the safety of the mother and fetus.